Bringing the Truth Home: the role of oral history and testimony in building and fragmenting Australian collective history and the Stolen Generations (NEW: Emerging scholars in Australian Indigenous Studies, 2018)
Australia’s fraught colonial past has made the search for a collective history exceptionally difficult; history wars surrounding policies of child removal in particular are a testament to the nation’s fractured memory. This essay examines the role of oral history in the promotion of both truth and healing – not only for separated Indigenous families, but also for the collective national identity which has suffered as a result of colonial Australia’s failure to pay heed to Indigenous voices.KeywordsStolen Generations; history wars; oral history